The glutamate carboxypeptidase AMP1 mediates abscisic acid and abiotic stress responses in Arabidopsis. Issue 1 (29th April 2013) - Shi, Yiting; Wang, Zheng; Meng, Pei; Tian, Siqi; Zhang, Xiaoyan; Yang, Shuhua
Summary: ALTERED MERISTEM PROGRAM1 ( AMP1 ) encodes a glutamate carboxypeptidase that plays an important role in shoot apical meristem development and phytohormone homeostasis. We isolated a new mutant allele of AMP1, amp1‐20, from a screen for abscisic acid (ABA) hypersensitive mutants and characterized the function of AMP1 in plant stress responses. amp1 mutants displayed ABA hypersensitivity, while overexpression of AMP1 caused ABA insensitivity. Moreover, endogenous ABA concentration was increased in amp1‐20 ‐ and decreased in AMP1 ‐overexpressing plants under stress conditions. Application of ABA reduced the AMP1 protein level in plants. Interestingly, amp1 mutants accumulated excess superoxide and displayed hypersensitivity to oxidative stress. The hypersensitivity of amp1 to ABA and oxidative stress was partially rescued by reactive oxygen species (ROS) scavenging agent. Furthermore, amp1 was tolerant to freezing and drought stress. The ABA hypersensitivity and freezing tolerance of amp1 was dependent on ABA signaling. Moreover, amp1 had elevated soluble sugar content and showed hypersensitivity to high concentrations of sugar. By contrast, the contents of amino acids were changed in amp1 mutant compared to the wild‐type. This study suggests that AMP1 modulates ABA, oxidative and abotic stress responses, and is involved in carbon and amino acid metabolism in Arabidopsis .